EFEKTIVITAS BUDAYA ORGANISASI DALAM MEMACU INOVASI PENDIDIKAN ISLAM : Studi Pada Pesantren Modern Al-Junaidiyah Biru Kabupaten Bone (Universitas Majalengka, 2022)
This research determines the effectiveness of organizational culture in spurring Islamic education innovation in Al Junaidiyah Biru Modern Pesantren. This research is field research that uses qualitative methods with observation, interview, and documentation techniques. For the data analysis process, three analysis components are used whose activities interact with each other in data collection, namely: 1). data reduction, 2). presentation of data, and 3). conclusion withdrawal and verification. The results showed that organizational culture in The Modern Al-Junaidiyah Biru Boarding School refers to three approaches: the traditional approach, the modernist approach, and the local culture approach Bugis Bone. It was born so-called the culture of sincerity, transparency, trust, siri, sipakatau, and sipakainge as a form of implementation of organizational culture in The Modern Pesantren Al Junaidiyah Biru